The Ordovician strata of the Ennedi Plateau, northeastern Chad (Erdi Basin) - Ghienne, Jean-François; Moussa, Abderamane; Saad, Abakar; Djatibeye, Barnabé; Youssouf, Hissein Mahamat (Comptes Rendus. Géoscience)
In the Ennedi Plateau, northeastern Chad, Cambrian(?)–Ordovician to Carboniferous strata represent one of the most proximal succession of the north-facing Gondwana platform. This study presents preliminary results related to the c. 200 m-thick Lower Sandstones and overlying Bedo Formation, which essentially record Early to Middle Ordovician flooding events and the end-Ordovician glaciation and subsequent deglaciation. In the Lower Sandstones, fluvial-dominated deposits (prevailing cross-stratification, NW to NNE paleocurrent trends) include intervening high-frequency marine incursions (tidal deposits, ichnofacies including Cruziana and Arthrophycus). Above an erosional unconformity, the end-Ordovician glacial record consists of fluvioglacial conglomeratic deposits atop the Lower Sandstones, which are in turn superimposed by the fine-grained Bedo Formation. The latter interval, onlapping an exhumed erosion surface showing north-trending km-scale glacial lineations, shows glaciomarine deposits only at its base and possibly include Lower Silurian deposits in its upper part.